2024
DOI: 10.1186/s13287-023-03626-8
|View full text |Cite
|
Sign up to set email alerts
|

Good manufacturing practice production of human corneal limbus-derived stromal stem cells and in vitro quality screening for therapeutic inhibition of corneal scarring

Mithun Santra,
Moira L. Geary,
Elizabeth Rubin
et al.

Abstract: Background Mesenchymal stem cells in the adult corneal stroma (named corneal stromal stem cells, CSSCs) inhibit corneal inflammation and scarring and restore corneal clarity in pre-clinical corneal injury models. This cell therapy could alleviate the heavy reliance on donor materials for corneal transplantation to treat corneal opacities. Herein, we established Good Manufacturing Practice (GMP) protocols for CSSC isolation, propagation, and cryostorage, and developed in vitro quality control (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Flow cytometry analysis showed that equine CSSCs presented a high expression of the surface markers CD44 (98.03%), CD45 (98.73%), and CD90 (97.97%) and low expression of CD200 (4.85%) (Figure 2A), confirming their mesenchymal origin. Then, the effect of EVs on cells' stemness under ER stress conditions was evaluated by measuring by qRT-PCR the expression of the markers SOX2, KLF4, OCT4, and NANOG, known to be expressed in CSSCs [18,76,77]. For RT-qPCR, first, CSSCs were treated with tunicamycin to induce ER stress, increasing the gene expression levels of SOX2, KLF4, and OCT4 (Figure 2B-D).…”
Section: Effect Of Evs On Csscs Cells' Stemnessmentioning
confidence: 99%
“…Flow cytometry analysis showed that equine CSSCs presented a high expression of the surface markers CD44 (98.03%), CD45 (98.73%), and CD90 (97.97%) and low expression of CD200 (4.85%) (Figure 2A), confirming their mesenchymal origin. Then, the effect of EVs on cells' stemness under ER stress conditions was evaluated by measuring by qRT-PCR the expression of the markers SOX2, KLF4, OCT4, and NANOG, known to be expressed in CSSCs [18,76,77]. For RT-qPCR, first, CSSCs were treated with tunicamycin to induce ER stress, increasing the gene expression levels of SOX2, KLF4, and OCT4 (Figure 2B-D).…”
Section: Effect Of Evs On Csscs Cells' Stemnessmentioning
confidence: 99%
“…Our group recently reported that the stromal recovery by CSSCs was further improved by an additional CSK injection treatment, which strengthens the healing stroma with proper collagen types and stromal specific proteoglycans [ 9 ]. Building upon these numerous positive outcomes from pre-clinical studies, we established clinical-grade human CSSC manufacturing with GMP-compliant protocols [ 99 ]. The stem cell phenotypes and the characteristic capability to differentiate into CSKs were confirmed.…”
Section: Cell-based Approach For Corneal Wound Healing and Scar Manag...mentioning
confidence: 99%
“…The stem cell phenotypes and the characteristic capability to differentiate into CSKs were confirmed. In addition, we developed an important quality management system using in vitro quality control assays for primary CSSCs screening to identify their in vivo anti-scarring potency and effectiveness [ 99 ]. The calculation of the Scarring Index (SI) in correlation to the in vivo scar inhibitory outcome has demonstrated that CSSCs with SI < 10 had a predicted 50% scar reduction potency while cells with SI > 10 were ineffective to control scarring and should be excluded for patient use (International PCT/US23/27823).…”
Section: Cell-based Approach For Corneal Wound Healing and Scar Manag...mentioning
confidence: 99%
See 1 more Smart Citation